Optimizing Digital Marketing Through Social Media In The Sewagati Go Digital Program - Dewi Widiawati; Juliedt Bunga Andarista; Rosa Dalima Gale; Alvindo Bani Pangga Leghu; Ika Wulandari; Prashanth Beleya; Teo Hui Thung (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program addresses the limited digital marketing skills among micro-business actors in Kelompok Wanita Tani (KWT) Sewagati Yogyakarta and the Malaysian partner community. Both groups of UMKM still rely on traditional marketing, lack consistent brand awarness, have limited packaging standards, and possess insufficient skills in digital content creation and data driven promotional strategies. Through the Sewagati Go Digital program, structured training sessions, workshops, mentoring, collaborative discussions with international partners, and hands on assistance were conducted to strengthen their capacity in social media optimization, content production, and digital ecosystem building. The results show significant improvements in branding consistency, increased posting frequency, better content quality, higher digital literacy, and the formation of a sustainable village digital community. This indicates that the program successfully enhanced the digital readiness and competitiveness of both communities, preparing them for broader markets, including the ASEAN region. text.